Improving Education in Agricultural Biosciences through Studying Abroad in the United States - Phillip R. Myer; David Ader; Tom Gill (Journal of Microbiology & Biology Education, 2019)
Studying abroad in agricultural biosciences can develop students’ cultural, academic, and communication skills and enhance employability. However, in the United States, discussions of study abroad are limited to either one-way directionality (U.S. students to other countries) or to the experiences of international students who come to the United States for degree programs. We analyzed the perspectives and experiences of studying abroad by Zamorano University (Honduras) students who completed an agricultural bioscience pasantía (four-month internship) during the final year of their undergraduate program. We used mixed methods to collect data via focus group discussions and a survey with Zamorano students who had completed a pasantía in 2017, as well as key informant interviews with Zamorano pasantía coordinators. Study-abroad experiences were compared between students who completed their pasantía in the United States (37%) and those who completed their pasantía in any of 17 other countries worldwide. Significant relationships were identified (p < 0.05) between: doing a pasantía in the United States (compared with going elsewhere) and improving science and theoretical knowledge; having a hands-on experience and science and theory improvement; improving communication and confidence in using scientific methods. The Zamorano pasantía model lends insights into the value of study abroad for agricultural bioscience education.